2018
DOI: 10.1111/obr.12680
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multidisciplinary interventions on weight loss and health outcomes in children and adolescents with morbid obesity

Abstract: There is not a 'one-size-fits-all' treatment approach, and matched care to personal needs is preferable. The integration of a chronic care approach is critical for the successful adaption of sustainable health behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
3
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 40 publications
3
67
3
5
Order By: Relevance
“…There is a diversity of intervention and prevention strategies . They extend from community‐based approaches to a range of parent‐focused strategies and multifaceted interventions . There is evidence of modest effects, claims of no effects, effects that are small, although statistically significant, but lack clinical significance and “patchy” progress on prevention .…”
Section: Introductionmentioning
confidence: 99%
“…There is a diversity of intervention and prevention strategies . They extend from community‐based approaches to a range of parent‐focused strategies and multifaceted interventions . There is evidence of modest effects, claims of no effects, effects that are small, although statistically significant, but lack clinical significance and “patchy” progress on prevention .…”
Section: Introductionmentioning
confidence: 99%
“…There has been consistent evidence that comprehensive medium-to high-intensity behavioral treatment interventions in adolescents with obesity and overweight result in at least short-term benefits. Specifically, meta-analyses (25)(26)(27)(28) have confirmed the efficacy of comprehensive, behavioral, familybased interventions for pediatric obesity previously reported in a Cochrane Review (29). One meta-analysis of 29 behavioral studies in youth up to age 18 years showed significant short-term effects on BMI outcomes in favor of treatment (standardized mean difference: −0.54; 95% CI: −0.73 to −0.36) (27).…”
Section: Evidence Base Of Intervention Efforts Among Adolescents Withmentioning
confidence: 67%
“…Pooled estimates for blood pressure and quality of life also showed significant improvement. A more recent meta‐analysis of 20 RCTs in youth up to age 18 examining behavioral interventions for obesity reached similar conclusions . The overall effect size for the interventions compared with controls was slightly lower but significant (Hedge’s g = 0.473; 95% CI: 0.362 to 0.584).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations